"I thought they'd do more": conflicting expectations of crowdfunding communication. Issue 2 (7th May 2019) - Levenshus, Abbey B.; Lemon, Laura L.; Childers, Courtney; Cho, Moonhee
Abstract : Purpose: The purpose of this paper is to explore the comprehensive, ongoing role of communication in an enterprise crowdfunding context, which has been largely overlooked. Design/methodology/approach: A large public higher education institution in the Southeastern USA was chosen as the case study unit to illuminate an enterprise-wide crowdfunding program using a proprietary, in-house platform, compared to commercial sites like Kickstarter that do not let organizational leaders strategically plan and manage the platform and its communication functions. Such autonomy provides a richer landscape for studying organizational members' communication and communication management related to an enterprise crowdfunding program. Findings: The case study identified communication-related challenges to the fundraising program's success such as limited project leader and funding recipients' commitment to communicate with their social networks about the projects. Internal communication and conflicting expectations, largely ignored in current crowdfunding research, were seen as critical to program effectiveness. Originality/value: This study adds scholarly and practical depth to knowledge of enterprise crowdfunding, a relatively new phenomenon in nonprofit and higher education fundraising. While not generalizable to all settings, findings can offer transferable guidance for organizations seeking to engage internal stakeholders related to new and innovative fundraising programs that require their active buy-in and participation.